Helpful and Hindering Factors in Psychodrama Field Training: A Longitudinal Mixed Methods Study of Student Development - Azoulay, Bracha; Orkibi, Hod (Frontiers in Psychology, 2018)
Although the literature indicates that students in mental health professions start to form their professional identity and competence in graduate school, there are few studies on the in-training experience of creative arts therapies students. This mixed-methods study examined how five first-year students in a psychodrama master’s degree program in Israel experienced their field training, with the aim of identifying the factors likely to promote or hinder the development of their professional identity and sense of professional ability. Longitudinal data were collected weekly throughout the 20-week field training experience. The students reported qualitatively on helpful and hindering factors and were assessed quantitatively on questionnaires measuring professional identity, perceived demands-abilities fit, client involvement, and therapy session evaluations. A thematic analysis of the students’ reports indicated that a clear and defined setting and structure, observing the instructor as a role model, actively leading parts of the session, and observing fellow students were all helpful factors. The hindering factors included role confusion, issues related to coping with client resistance and disciplinary problems, as well as school end-of-year activities that disrupted the continuity of therapy. The quantitative results indicated that students’ professional identity did not significantly change over the year, whereas a U-shaped curve trajectory characterized the changes in demands-abilities fit and other measures. Students began their field training with an overstated sense of ability that soon declined and later increased. These findings provide indications of which helping and hindering factors should be maximized and minimized, to enhance students’ field training.